Diet Survey of The Families in A Rural Area- An Observational Study - Richa Nigam; Sonia Tiwari (Medsci Publications, 2015)
Background: Surveys to assess the dietary intake and nutritional status of population are essential to monitor the ongoing nutrition transition and initiate appropriate intervention. Looking into the higher prevalence of problem in rural areas, additional surveys at smaller level are required for monitoring of food security.1 Objec- tives of the study were to assess nutritional status of families us- ing diet survey method and to find out determinants of food availability in families under study. Methods: This is a community based study was done under the department of Community Medicine at Sri Aurobindo Medical College and P.G. Institute Indore, after taking approval from eth- ics and research committee of the institute. Two stage cluster sampling was done for the survey. A dietary survey based on 24 hour recall of food consumption in the families of a rural area was done. Results: The mean calorie/CU in class I by( Prasad's socio- economic classification was 1910.11 and of class IV was 1597.53 (p-0.007).The mean protein /CU was found to be 93.48, 71.49, 67.46 and 61.60 in socio-economic class I,II,III and IV respectively (p<0.001). Conclusions: The mean calorie and protein per consumption unit in the families was found to be dependent on the socio-economic status (SES).Whereas the type of family didn't have much role with the calorie and protein intake per consumption unit.